Dinámica afectiva familiar y su relación con el bajo rendimiento académico en los estudiantes del Primer Año de Bachillerato del Colegio 27 de Febrero de la ciudad de Loja en el periodo junio-noviembre 2014 - Salazar Condolo, Luis Miguel (2015)
The affective familiar dynamic constitutes the prior base in individual’s development and it has repercussions on its growth. In this study the affective familiar dynamic is analyzed, which is related with the low academic grades. It had as main objective to determine the relationship that exists between biopsychosocial factors that generate reactions in the affective familiar dynamic. And, as specific objectives, the facts referred to the academic development of students with low grades from the first year of Bachillerato at “27 de Febrero” High School in Loja. In addition, it has a therapeutic plan directed to strengthen learning in students with low grades and link it to their families during learning process. This is based on the use of a dynamic methodology for suitable communication between parents, children and teachers; familiar permeability in the teaching process, and role establishment at home for the accomplishment of scholar tasks in their children. In the field study, the methodological process applied was based on the use and empiric application of techniques and instruments over a population of 217 students. Having as sample 103 students of the first year of Bachillerato at “27 de Febrero” High School, who fulfilled with inclusion criteria, resulting that 41% of them belong to dysfunctional families and 18% belong to moderately dysfunctional ones. These results trigger low grade problems in teenagers that study in this High School. In response to this fact, it was raised a Therapeutic plan as a solution, which aims to improve family dynamic sand strengthen affective learning. Key words: Individual growth, development, moderately dysfunctional, therapeutic plan.